PENGARUH CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, KEPEMILIKAN MAYORITAS, DAN CORPORATE GOVERNANCE TERHADAP AGRESIVITAS PAJAK (studi empiris pada perusahaan pertambangan dan pertanian yang terdaftar di BEI tahun 2014-2016) - Rafiqah Ratu; Nasrizal Nasrizal; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study is aims to analyze and provide empirical evidence of the influence of corporate social responsibility, leverage, majority ownership and corporate governance of tax aggressiveness. The population is used to mining and agricultural companies listed on the Indonesian stock exchanges for the period 2014-2016. The sampling method is purposive sampling with result of selection of 45 data. Data analysis is used by multiple linear regression. For analysis the hypothesis of these variabel is using SPSS 22. The results of this study proves corporate social responsibility does not affect the aggressiveness of taxes with a significant value of 0.124 and tcount 1.570 ttable 2,021. Majority ownership has no effect on tax aggressiveness with significant value 0.807 and tcount 0.242 ttable 2,021. Coefficient of determination on this research is 0,349 that means 34,9% influence of tax aggressiveness explained by variable of corporate social responsibility, leverage, majority ownership and corporate governance. The remaining 65.1% is explained by other variables.Keyword : Corporate Social Responsibility, Leverage, Majority ownership, Corporate Governance and Tax Aggressiveness.